Countering Technotronic Ethnocide through Digital Communication Ethics in the Era of Social Media - Ferdiana .; Yuli Hidayati (CV. ITTC INDONESIA, 2026)
This study examines the issue of ethical degradation in communication on social media within the context of globalization and technological acceleration, which together give rise to the threat of technetronic ethnocide. The purpose of this research is to gain an in-depth understanding of these phenomena through a reflective approach in order to formulate a foundation of digital communication ethics that is relevant to the dynamics of contemporary society. This research employs a qualitative method with a descriptive reflective character within an interpretive–critical paradigm and adopts a library research design through literature reviews and the analysis of relevant documents. The analytical technique used is conceptual thematic analysis, which involves identifying issues, categorizing themes, interpreting meanings, and conducting reflective synthesis to generate a more comprehensive conceptual understanding. The findings indicate that social media is ambivalent in nature: on the one hand, it expands public participation, while on the other hand it accelerates the spread of hoaxes, hate speech, identity-based polarization, and the erosion of communicative civility. Referring to Eric Voegelin’s distinction between substantive and pragmatic communication, this study emphasizes the importance of strengthening communication ethics and digital literacy in order to balance freedom of expression with social responsibility.